Cilostazol decreases total atrial conduction time in patients with peripheral artery disease. (May 2014) - Alizade, E; Şahin, M; Şimşek, Z; Açar, G; Bulut, M; Güler, A; Avcı, A; Kalkan, ME; Pala, S; Akçakoyun, M; Esen, AM
Objective: Total atrial conduction time (TACT) is the most important parameter in predicting the development of new-onset atrial fibrillation. We investigated the effect of cilostazol therapy on TACT in patients with peripheral artery disease. Methods: Thirty patients with peripheral artery disease were treated with cilostazol (200 mg/day) for 6 months. The baseline echocardiographic total atrial conduction time parameter was compared with the 6-month follow-up. Results: The TACT duration was decreased in all patients compared with the baseline after therapy (121.8 ± 19.3 vs. 109.1 ± 15.9 milliseconds, p<0.001). However, left atrial (LA) diameter was not changed with the therapy. The reduction of TACT duration was correlated with the increase in mitral E wave velocity/mitral A wave velocity ratio (r=-0.48, p<0.003). Conclusion: Our results showed that 200 mg cilostazol treatment decreased TACT duration in patients with peripheral artery disease, which may also prevent the development and/or recurrence of atrial fibrillation (AF).